Pulmonary aspiration during pregnancy or immediately postpartum in the UK: A population-based case-control study [version 1; peer review: 2 approved] - Ruth Tunn; Marian Knight; Alison Gooda; Nuala Lucas (NIHR Open Research)
Background Pulmonary aspiration of gastric contents is the most frequent cause of death associated with complications of airway management during general anaesthesia. Pregnancy increases aspiration risk owing to factors including delayed gastric emptying and increased intragastric pressure. We describe the incidence, risk factors, management, and outcomes of maternal pulmonary aspiration in pregnancy in the UK. Methods We conducted a population-based surveillance and case-control study. Between September 2013 and August 2016, all UK consultant-led obstetric units prospectively identified cases of pulmonary aspiration among parturient women using a pre-defined case definition, and reported them via the UK Obstetric Surveillance System (UKOSS). Controls (n=1982) were obtained from four UKOSS studies conducted between 2005 and 2014. We calculated the incidence of pulmonary aspiration using 2013–2015 maternities as the denominator. We explored potential risk factors for aspiration using univariable logistic regression and described outcomes. Results We identified 12 cases of pulmonary aspiration, giving an incidence of 5.2 per 1,000,000 maternities (95% CI 2.69-9.09). Cases were significantly less likely than controls to be multiparous (unadjusted odds ratio [uOR] 0.255, 95% CI 0.069-0.946), and significantly more likely to undergo caesarean section (uOR 24.89, 95% CI 3.18-194.85) and to receive general anaesthetic for caesarean section (p<0.001). Gestation was significantly shorter in cases than controls (uOR 0.782, 95% CI 0.702-0.870). Women who aspirated were significantly more likely to be admitted to the intensive therapy unit than controls (p<0.001). Infants of women who aspirated had significantly lower Apgar scores and were more likely to be admitted to the neonatal intensive care unit or to be stillborn compared with infants of women in the control group. Conclusions Pulmonary aspiration is rare in UK obstetric anaesthetic practice; however, it remains a risk of general anaesthesia. Despite a large study population, our analyses lacked power to evaluate many potential risk factors. Future research should focus on developing methods to accurately identify pregnant women at risk of aspiration.